Financial Distress Among Older Adults With Cancer. Issue 6 (June 2021) - Giri, Smith; Clark, Deanna; Al-Obaidi, Mustafa; Varnado, Will; Kumar, Seema; Paluri, Ravi; Gbolahan, Olumide; Bhatia, Smita; Williams, Grant R.
Abstract : PURPOSE: Financial distress (FD) among older adults with cancer is not well studied. We sought to characterize prevalence and factors associated with FD among older adults with cancer and the association of FD with geriatric assessment (GA) –identified deficits. PATIENTS AND METHODS: We included adults age ≥ 60 years with cancer in the University of Alabama at Birmingham Cancer and Aging Resilience Evaluation Registry who underwent GA during initial consultation with a medical oncologist before starting systemic therapy. We captured FD using a single-item question: "Do you have to pay for more medical care than you can afford?" We built multivariable models to study the impact of sociodemographic/clinical factors on FD as well as the association of FD with GA impairments. RESULTS: We identified 447 older adults with a median age of 69 years; 60% were men, 75% were White, and colorectal (26%) and pancreatic (19%) cancers were the most common. Overall, 27% (n = 121) reported having FD. Factors associated with FD included being Black (v White; odds ratio [OR], 2.26; 95% CI, 1.35 to 3.81; P = .002), being disabled/unemployed (v employed; OR, 2.60; 95% CI, 1.17 to 5.76; P = .019), and having an advanced degree ( v less than high school; OR, 0.13; 95% CI, 0.03 to 0.65; P = .012). Patients with FD were more likely to report several GA impairments, including depression (OR, 2.10; 95% CI, 1.06 to 4.18; P = .034) and impaired health-related quality of life in physical (β = −2.82; P = .014) and mental health domains (β = −3.31; P = .002). CONCLUSION: More than a quarter of older adults with cancer reported FD at the time of initial presentation to an oncologist. Several demographic factors and GA impairments were associated with FD.